Blackbeard : - Konstam, Angus (Wiley, 2006)
Drawing on vivid descriptions of Blackbeard's attacks from his rare surviving victims, pirate expert Angus Konstam traces Blackbeard's career from its beginnings to his final defeat in a tremendous sea battle near his base at Ocracoke Island. Presenting dramatic accounts of the pirate's very effective tactics and his reputation for cruelty, Konstam offers a fascinating examination of the life and business of piracy and the lure of this brutal and bloody trade.